Impacts of experiences during supervised internship in a family health unit in the context of the COVID-19 pandemic (Research, Society and Development, 2023)
The Supervised Internship is a curricular component of undergraduate nursing that aims to bring nursing students as close as possible to professional life, through a participatory teaching-learning process rich in experiences that unite theory and practice. The aim of the present study is to describe the experiences of nursing students in the context of the COVID-19 pandemic, during the mandatory curricular component Supervised Internship I, in a Family Health Unit (FHU). This is a descriptive and qualitative study, of the type of experience report, carried out from the experiences of nursing students, in the context of the COVID-19 pandemic, during the supervised internship, in a Family Health Unit, located in a city in the interior of Bahia. The activities performed involved Health Planning, Unit Management and care, and were carried out progressively, as the students acquired autonomy and confidence. The nurses experienced limiting factors for the enrichment of the teaching-learning process, such as the reduction of the internship workload and the reduction of the flow of patients to perform nursing consultations. Despite the limitations, the experiences obtained during the internship allowed the acquisition and development of personal and professional skills, strengthening critical thinking and theoretical-practical articulation.